2019
DOI: 10.1111/pops.12577
|View full text |Cite
|
Sign up to set email alerts
|

Negative Intergroup Contact and Radical Right‐Wing Voting: The Moderating Roles of Personal and Collective Self‐Efficacy

Abstract: This study examines whether negative contact with immigrants promotes voting for radical right‐wing parties, to what extent this relationship can be explained by feelings of outgroup threat, and whether this relationship depends on perceived personal and collective self‐efficacy. Hypotheses were tested among 630 native Dutch respondents, mainly living in multicultural neighborhoods. The results show that negative contact with immigrants is associated with feelings of personal (egocentric) and group (sociotropi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…Similarly, studies indicate that positive contact with immigrants should be more likely to reduce the perception of threat while negative contact with immigrants should be more likely to increase it (see Aberson, 2019 for a meta‐analysis; Aberson & Gaffney, 2009; Corenblum & Stephan, 2001; Curşeu et al., 2007; Stephan et al., 2000). Ingroup members who have positive contact experiences with immigrants may be less attracted and responsive to the anti‐immigrant messages of right‐wing parties (Nijs et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, studies indicate that positive contact with immigrants should be more likely to reduce the perception of threat while negative contact with immigrants should be more likely to increase it (see Aberson, 2019 for a meta‐analysis; Aberson & Gaffney, 2009; Corenblum & Stephan, 2001; Curşeu et al., 2007; Stephan et al., 2000). Ingroup members who have positive contact experiences with immigrants may be less attracted and responsive to the anti‐immigrant messages of right‐wing parties (Nijs et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…According to Rydgren (2008, p. 739), radical right parties tend to frame immigrants as follows: (1) a threat to the national identity (2) a major cause of criminality and social unrest (3) a cause of unemployment, and (4) abusers of the welfare state. Often, this is appealing to those who are afraid of social and economic changes in society (Criss, 2020) or feel threatened Nijs et al., 2019). Some studies have proven that exposure to such messages and images that represent immigrants as different and a danger to the society can lead to more negative cognition toward immigrants among ingroup members (Wirz et al., 2018), negative stereotypes about immigrants, and intergroup anxiety (Matthes & Schmuck, 2017), and are effective at mobilizing voter support for radical‐right (Rydgren, 2008).…”
Section: Introduction/backgroundmentioning
confidence: 99%
“…As contact opportunities may lead to both positive and negative contact, it may be that the same voters who experienced an increase in positive contact also experienced an increase in negative contact and that the impact of negative contact experiences on voting intentions was more severe. A recent study showed that negative contact experiences predict support for the PVV, even after controlling for indicators of threat [ 50 ].…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Studies that focused on the impact of intergroup contact on radical right voting seem to provide support for both the positive contact mechanism [ 11 , 14 , 29 ] (but see also Savelkoul and Scheepers [ 49 ]) and the negative contact mechanism (Nijs et al . [ 50 ]). However, the presence of asylum seekers in ASCs may not always provide the most favourable opportunities for sustained positive interactions [ 20 ].…”
Section: Theoretical Expectationsmentioning
confidence: 99%
“…Going beyond intergroup attitudes, recent research showed that outgroup threat predicted collective action against immigrants and immigration in various intergroup settings (Caricati et al, 2017; Hasbún López et al, 2019; Nijs et al, 2019; Shepherd et al, 2018): For instance, negative contact with immigrants was associated with feelings of threat and lead to the support of right‐wing parties and their anti‐migration policies (Nijs et al, 2019). In addition, survey data from 11 European countries showed that feeling threatened by refugees predicted collective action that supports restrictions against further refugee influx and policies to expel refugees (Hasbún López et al, 2019).…”
Section: Introductionmentioning
confidence: 99%